ISOLATION OF TWO FLAVONOIDS FROM BAUHINIA MONANDRA (KURZ) LEAVES AND THEIR ANTIOXIDATIVE EFFECTS - Aderogba, M. A.; Ogundaini, A. O.; Eloff, J. N. (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
Bauhinia monandra (Kurz), traditionally use in the treatment of diabetes with established significant anti-diabetic activity was investigated for its antioxidant constituents since the activity demonstrated can be linked to the presence of antioxidant compounds. Bioassay directed fractionation of the ethyl acetate soluble leaves extract has led to isolation of two active compounds identified as: Quercetin-3-O-rutinoside (1) and Quercetin (2). The molecular structures elucidations of both compounds were carried out using spectroscopic studies (1H NMR, 13C NMR and MS). These compounds are reported from this species for the first time. A DPPH spectrophotometric assay was used to evaluate the antioxidant potential of the compounds. Compound 2 had higher antioxidant activity while Compound 1 had lower activity than L-ascorbic acid which was used as